KEPEMIMPINAN KEPALA SEKOLAH DAN KAITANNYA DENGAN UPAYA PENINGKATAN MUTU PENDIDIKAN DI SLB BHAKTI PERTIWI BOKOHARJO PRAMBANAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
Â This study aims to describe (1) the program planning of principal (2) the implementation of program planning of principal. (3) the evaluation conducted by the principal and related to effort the improvement of the quality of education in SLB Bhakti Pertiwi.This study used a qualitative approach; the data source comes from informants included: principal, vice-principals, teachers, staffs, parents, school committees, and documents related to the effort of the improvement of the quality of education. The date collection technique be used were in-depth interviews, participant observation, and documentation. While the testing the validity of the date carried out by the observations of extension, the increase of persistence, the using of reference materials, and tri-angulations.The result of the research shows that the planned program, the implementation of the planned program and also the evaluation of the planned program which is committed by the principal is suitable with the eight national standard of education. The skill training which is conducted in school is a program that has purpose to form the student to be more independent and this is suitable with the main mission of the school. The school already has the curriculum based on educational level and also appropriate teaching media. The method has been appropriate to the need of the students, the process of teaching suits with the guidance of educational department and also supported by appropriate facilities and infrastructure, qualified teacher and school committee who always support the program. The existing obstacles are; the initiative and the attention of the studentâ€™s parents are less than what it is supposed to be. The establishment of the dormitory for the students is also still face a problem. The way to solve that problem is by conducting a briefing to the parents and also initiate a proposal to the government of Yogyakarta to build the dormitory.Â